The Influence of Competence and Motivation on Employee Performance - Putri Aziziah; Diana, Deti; Anugrah, Siti Amelia Nur; Kartono, Kartono (Indonesian Journal of Business Analytics, 2024)
The purpose of this study is to investigate how motivation and competence affect worker performance. This study employed a quantitative descriptive research design. The 74 participants in this study were all workers at Bappelitbangda Cirebon City. For the variables of competency, motivation, and employee performance, this research data collection technique uses interview and questionnaire methods with statement items. The study's findings demonstrate that employees at Cirebon City Bappelitbangda perform better and more significantly when they are competent. There is no discernible correlation between employee motivation and performance at Cirebon City Bappelitbangda. Employee performance at Cirebon City Bappelitbangda is positively and significantly impacted by both competence and motivation at the same time.